Pendekatan dalam Kajian Filsafat Pendidikan Islam - Akbar, Aziz (Universitas Islam Internasional Darullughah Wadda'wah, 2024)
The approach in the study of Islamic educational philosophy referred to in this research is an approach in understanding its application. In this article, we will explain the general meaning of philosophy, the meaning of Islamic educational philosophy, philosophical analysis of educational problems, the objects of philosophical study and approaches to the study of Islamic educational philosophy. In the philosophy of education, many new things will be discovered which will certainly add to the scientific insight possessed by every researcher. Apart from that, educational philosophy provides direction so that the educational theories that are developed have relevance to real life, in other words directing that the theories and views of the educational philosophy that have been developed can be applied in educational practice in accordance with the realities and needs of life that are also developing in society.